Antagonistic activity of Trichoderma sp. against pathogens in the leaves of Allium ascalonicum L. - Maulana, Indra; Lubis, Syafrina S.; Harahap, Diannita; Arskadius, Nasyaya U.; Concepcion, Ronnie S. (Narra Sains Indonesia, 2024)
Pathogenic fungi pose constraints and reduce shallot production. Trichoderma sp. is an antagonistic fungus capable of controlling pathogen growth in shallots. The aim of this study was to determine the characteristics of Trichoderma sp. and pathogens in shallots and to assess the antagonistic ability of Trichoderma sp. against shallot pathogens (Allium ascalonicum L.). Trichoderma sp. and shallot pathogens were isolated using a serial dilution agar plate method using potato dextrose agar medium with 7-day incubation. The antagonistic activity of Trichoderma sp. against shallot pathogens was evaluated based on the dual culture method. In this study, we successfully isolated Trichoderma harzianum from the shallot leaf and its root systems. Moreover, four morphologically distinctive pathogens from shallot roots and leaves were successfully isolated (l Aspergillus sp., Colletotrichum sp., Phytium sp. and Penicillium sp. T. harzianum was found to have the ability to inhibit 23.45% growth of Aspergillus sp, 26.19% growth of Colletotrichum sp., 75.40% growth of Phytium sp., and 40.38% growth of Penicillium sp. In conclusion, the isolated T. harzianum had a strong antagonistic activity against some pathogens in the shallot, but the activity was weak against some others.